ECONOMIC EFFICIENCY AND SUSTAINABILITY FROM A NATIONAL LEGAL PERSPECTIVE: A LITERATURE REVIEW ON THE ROLE OF SECTOR REGULATION AND STATE-OWNED ENTERPRISES IN REALISING INCLUSIVE AND SUSTAINABLE GROWTH - Gunawan Widjaja (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
This article examines economic efficiency and sustainability from a national legal perspective through a literature review of the role of sector regulation and state-owned enterprises (SOEs) in achieving inclusive and sustainable growth. Sector regulation is seen as a legal instrument to correct market failures, ensure legal certainty, and encourage the application of sustainability and inclusivity principles through environmental, social, and governance standards. On the other hand, SOEs act as development agents that integrate commercial and social functions, support economic stability, and reduce environmental footprints through green economy practices and more transparent sustainability reporting. The results of the study show that sector regulation and SOEs are two main pillars that must be designed in an integrated, accountable manner and based on the principle of equitable efficiency within the framework of economic democracy to achieve inclusive and sustainable growth.